Avaliações socioeconômicas e ambientais de propriedades agrícolas e entendimento ambiental de produtores rurais no Município de Floreal - SP - Delmilho, Gustavo; Sergio Luis de Carvalho,; Miguel Spolon Fávaro, (Revista de Tecnologia & Gestão Sustentável, 2022)
The term sustainability is in global evidence. It is an inescapable topic when discussing agribusiness, productivity, preservation of fauna, flora, climate, use of natural resources, waste disposal, among others. However, ways to improve this scenario are shown through the use of environmental education and community awareness. This work, in particular, aimed to evaluate the social, economic and environmental aspects of rural properties in the Municipality of Floreal - SP, as well as the perception of farmers. Questionnaires were applied to 40 producers containing 26 questions with different answers, addressing environmental issues and how they are treated. Factors such as: family composition, forms of work performed, and use of technologies were evaluated. Agricultural production was also estimated, in addition to factors resulting from these activities, such as production technologies, machinery used, soil conservation and riparian forests. From the answers, problems were revealed, as an example: lack of environmental perception, in addition to little relevance on the part of producers in this context. Another issue of paramount importance is the consequences, such as contamination of the environment, misuse of water resources present, among others. In the end, there was a lack of environmental education programs that would provide rural producers with a balanced view of managing their activity, without neglecting the safety of their own health and the environment in which they live.